Rethinking ADHD intervention trials: feasibility testing of two treatments and a methodology - Fibert, Philippa (Eur J Pediatr, 2019)
Attention deficit hyperactivity disorder (ADHD) is a lifelong condition associated with considerable costs. The long-term effectiveness and acceptability of treatments to improve outcomes remains in doubt. Long-term trials are needed comparing interventions with standard care and each other. The Sheffield Treatments for ADHD Research (STAR) project used the Trials within Cohorts (TwiCs) approach. A cohort of children with ADHD was recruited and outcomes collected from carers and teachers. A random selection was offered treatment by homoeopaths (hom) or nutritional therapists (NT). Their outcomes (Conners Global ADHD Index) were compared with those not offered interventions. The feasibility of the methods and interventions was assessed. The TwiCs approach was feasible with modifications. 144 participants were recruited to the cohort, 83 offered treatment, 72 accepted, and 50 attended 1+ appointments. Results according to carers assessments at 6 months were as follows: t = 1.08, p = .28 (− 1.48, 4.81) SMD .425 (hom); t = 1.71, p = .09 (− .347, 5.89), SMD = .388 (NT). Teachers’ responses were too few and unstable. No serious treatment adverse events occurred. Conclusion: the STAR project demonstrated the feasibility of the TwiCs approach for testing interventions for children with ADHD.